1976
DOI: 10.1056/nejm197609232951303
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Content in the Bronchial Washings of Patients with Benign and Malignant Pulmonary Disease

Abstract: The bronchial washings of 58 patients with benign and neoplastic conditions involving the lungs were evaluated for immunoglobulin content. Levels in the washings from the diseased lung were compared with those from the normal contralateral lung. In normal patients and those with either bilateral inflammatory diseases or unilateral bronchiectasis or tuberculosis, the mean variation in igA/K and igG/K ratios between diseased and uninvolved lungs was minimal. In unilateral pneumonitis, however, igG/K was markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…A set of seven genes of the signature encoding several structural units of immunoglobulin along with the overexpression of the B lymphocyte chemoattractant gene CXCL13 suggests the significant role that humoral immunity plays during the development of NSCLCs. These findings are also backed by the prior work showing altered local immunoglobulin production in bronchial washing fluid collected from the lung segments in which lung cancer tumors are located as compared to the normal contralateral lung segments ( 61 ). Previous studies have reported the positive impact of IGKC on the survival of early stage NSCLC, in which stroma-infiltrating plasma cells were identified as the likely source of the IGKC ( 26 ).…”
Section: Discussionsupporting
confidence: 58%
“…A set of seven genes of the signature encoding several structural units of immunoglobulin along with the overexpression of the B lymphocyte chemoattractant gene CXCL13 suggests the significant role that humoral immunity plays during the development of NSCLCs. These findings are also backed by the prior work showing altered local immunoglobulin production in bronchial washing fluid collected from the lung segments in which lung cancer tumors are located as compared to the normal contralateral lung segments ( 61 ). Previous studies have reported the positive impact of IGKC on the survival of early stage NSCLC, in which stroma-infiltrating plasma cells were identified as the likely source of the IGKC ( 26 ).…”
Section: Discussionsupporting
confidence: 58%
“…Mandel et al [12] evaluated the immunoglobulin content in bronchial washings from patients with neo plastic diseases and compared them with those from the normal contralateral lung. The aim of the present study is the detection of IgA synthesis in vitro in speci mens of normal bronchial mucosa and bronchogenic carcinoma, obtained in most of the cases with standard bronchoscopic biopsy and to determine whether the IgA content could be used as a screening test for pa tients with suspect pulmonary masses and for early detection of recurrent carcinoma.…”
mentioning
confidence: 99%
“…Several studies have attempted to employ secretory IgA as well as 7S serum IgA in measurements of mucosal surface antibodies (7,8,14,15). In one recent report, underestimation of IgA concentration in tears was found when a com- mercially prepared liS IgA preparation was compared with a commercial 7S serum IgA standard (5).…”
mentioning
confidence: 99%